Analysis of the negative dynamics in the level of physical training of medical university students in the first four years of study - Safronov R.V.; Vanina E.S.; Pershikov S.V.; Nemchenko I.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to theoretical and practical evidence for alterations in the physical fitness of students throughout their time at a medical university. Methods and structure of the study. A series of tests was administered to evaluate the evolution of students’ physical condition over the course of their university studies. Results and conclusions. It was discovered that the physical fitness of students in their first and second years of university is average, but it reaches its peak in the second year. After that, in the third and fourth years, there is a sharp decline in physical fitness. Therefore, the authors concluded that after two years of study, students experience a significant decrease in their physical fitness, indicating that the third and fourth years of study are a crucial time for students’ health.